Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.29219/fnr.v66.7715
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity is associated with child’s dietary diversity score among primary school children in two districts in Ghana

Abstract: Background: Dietary diversity is generally considered as a good indicator of nutrient adequacy and is influenced by various factors at the national, household, and individual levels. Objective: The present study sought to determine the relationships between household food insecurity, primary caregivers’ nutrition knowledge, and dietary diversity of school-aged children in Ghana. Methods: This forms part of a longitudinal study conducted in the Ayawaso West Municipal district in Accra (urban setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Some studies (Bukania et al. , 2014; Chakona and Shackleton, 2017; Antwi et al. , 2022) show that many sub-Saharans consider quantity over quality; they have families to feed, so many times it is about making sure the household is satisfied and not necessarily adequately nourished.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies (Bukania et al. , 2014; Chakona and Shackleton, 2017; Antwi et al. , 2022) show that many sub-Saharans consider quantity over quality; they have families to feed, so many times it is about making sure the household is satisfied and not necessarily adequately nourished.…”
Section: Discussionmentioning
confidence: 99%
“…, 2017; Chakona and Shackleton, 2017; Onyeji and Sanusi, 2018), where a low consumption of fruits and vegetables (<30%) was recorded in Mexico, South Africa and Southeast Nigeria, respectively. A study among children in Ghana (Antwi et al. , 2022) also reported a low consumption of fruits, vegetables, animal protein and dairy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 20 ] Antwi J et al . [ 21 ] reported that FI at the household level was a predictor of the type of diverse diet that was consumed by primary school children in Ghana.…”
Section: Discussionmentioning
confidence: 99%